Impact of ns-DBD plasma actuation on the boundary layer transition using convective heat transfer measurements. (19th August 2015) - Ullmer, Dirk; Peschke, Philip; Terzis, Alexandros; Ott, Peter; Weigand, Bernhard
Abstract: This paper demonstrates that the impact of nanosecond pulsed dielectric barrier discharge ( ns -DBD) actuators on the structure of the boundary layer can be investigated using quantitative convective heat transfer measurements. For the experiments, the flow over a flat plate with a C4 leading edge thickness distribution was examined at low speed incompressible flow (6.6–11.5 m s −1 ). An ns -DBD plasma actuator was mounted 5 mm downstream of the leading edge and several experiments were conducted giving particular emphasis on the effect of actuation frequency and the freestream velocity. Local heat transfer distributions were measured using the transient liquid crystal technique with and without plasma activated. As a result, any effect of plasma on the structure of the boundary layer is interpreted by local heat transfer coefficient distributions which are compared with laminar and turbulent boundary layer correlations. The heat transfer results, which are also confirmed by hot-wire measurements, show the considerable effect of the actuation frequency on the location of the transition point elucidating that liquid crystal thermography is a promising method for investigating plasma-flow interactions very close to the wall. Additionally, the hot-wire measurements indicate possible velocity oscillations in the near wall flow due to plasma activation.